Revisão da preferência alimentar do boto-cinza (Sotalia guianesis) ao longo da costa do Brasil - Cesar, Marina Faucon Figueirêdo Fragoso [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Studying and understanding the feeding ecology of cetaceans is essential for the conservation and maintenance of these animals, since they are top predators of the trophic chain, as well as main indicators of the population dynamics of their prey and the health of the ecosystem in which they inhabit, in addition to bringing us valuable information about their distribution, migration patterns and behavior. Cetaceans feed on a wide diversity of prey, feeding both in coastal areas, such as bays and estuaries, and in oceanic regions – surface and bottom. Sotalia guianensis is a species of odontocete, of the Delphinidae family, and is found in almost all Brazilian coast. They have a high degree of residence, that is, they occupy the same areas throughout the year for reproduction, feeding and rearing of their young, which can be explained by the availability of prey in the region (Azevedo et al. 2004). The analysis of stomach contents to determine the diet is an important tool for greater knowledge not only of the predatory species, but also of its prey.

Estudar e compreender a ecologia alimentar de cetáceos é fundamental para a conservação e manutenção desses animais, já que são predadores de topo de cadeia trófica, além de principais indicadores da dinâmica populacional de suas presas e saúde do ecossistema em que habitam, além de nos trazer informações valiosas sobre sua distribuição, padrões de migração e comportamento. Os cetáceos se alimentam de uma ampla diversidade de presas, se alimentando tanto em áreas costeiras, como baías e estuários, quanto em regiões oceânicas – superfície e fundo. O Sotalia guianensis é uma espécie de odontoceto, da família Delphinidae, e é encontrado em quase todo litoral brasileiro. Possuem alto grau de residência, ou seja, ocupam as mesmas áreas o ano todo para reprodução, alimentação e criação de seus filhotes, o que pode ser explicado pela disponibilidade de presas na região (Azevedo et al. 2004). A análise do conteúdo estomacal para determinação da dieta é uma importante ferramenta para que haja o maior conhecimento não apenas da espécie predadora, mas também de suas presas.
Review of the feeding preference of the Guiana dolphin (Sotalia guianesis) along the coast of Brazil
Keywords: Cetáceo; Boto-cinza; Conteúdo estomacal; Otólitos